Oral intake of aripiprazole compromises male fertility in Drosophila. - Mukherjee, A.; Hurcomb, J.D.; Loh, S.H.Y.; Martins, L.M. (Biology Direct, 2025)
Antipsychotics have reported off-target effects, but their impact on subcellular organelles and cellular homeostasis in various organ systems is poorly understood. This study explored the off-target effects of aripiprazole on the male reproductive system using Drosophila as a model. Aripiprazole binds nonspecifically to mitochondrial complex I, and here we investigated the effect of an aripiprazole-containing diet on spermatogenesis. We showed that aripiprazole increases the level of mitochondrial reactive oxygen species (ROS) and disrupts the homeostasis of germ cell development in the testes. The cyst cells surrounding the spermatogonia showed an increase in JNK signalling, while there was enhanced LysoTracker staining of spermatogonial cysts and defects in the later stages of spermatid individualisation. Our results revealed a connection between mitochondrial complex I dysfunction and increased germ cell loss by lysosomal degradation, resulting in decreased fertility. We conclude that aripiprazole-induced mitochondrial toxicity in germ cells results in increased loss of spermatogonial cysts and defects in spermatogenesis. We showed that diets supplemented with antioxidants or the expression of mitochondrial superoxide dismutase in spermatogonial cells can alleviate excess mitochondrial ROS-induced defects. The online version contains supplementary material available at 10.1186/s13062-025-00698-9.